LAG-3 confers poor prognosis and its blockade reshapes antitumor response in head and neck squamous cell carcinoma. (1st November 2016) - Deng, Wei-Wei; Mao, Liang; Yu, Guang-Tao; Bu, Lin-Lin; Ma, Si-Rui; Liu, Bing; Gutkind, J. Silvio; Kulkarni, Ashok B.; Zhang, Wen-Feng; Sun, Zhi-Jun
ABSTRACT: Immunotherapy with immune checkpoint molecule-specific monoclonal antibody have obtained encouraging results from preclinical studies and clinical trials, which promoted us to explore whether this kind of immunotherapy could be applicable to head and neck squamous cell carcinoma (HNSCC). Lymphocyte activation gene-3 (LAG-3) is an immune checkpoint control protein that negatively regulates T cells and immune response. Here, using the human tissue samples, we report these findings that LAG-3 is overexpressed on tumor-infiltrating lymphocytes (TILs; p < 0.001) and its overexpression correlates with the high pathological grades, lager tumor size and positive lymph node status in human primary HNSCC. Survival analysis identifies LAG-3 as a prognostic factor independent of tumor size and pathological grades for primary HNSCC patients with negative lymph node status ( p = 0.014). Study in immunocompetent genetically defined HNSCC mouse model reports that LAG-3 is upregulated on CD4 + T cells, CD8 + T cells and CD4 + Foxp3 + regulatory T cells (Tregs). In vivo study, administration of LAG-3-specific antibody retards tumor growth in a way associated with enhanced systemic antitumor response by potentiating the antitumor response of CD8 + T cells and decreasing the population of immunosuppressive cells. Taken together, our results offer a preclinical proof supporting the immunomodulatory effects of LAG-3 and suggest a potential therapeutic target of immunotherapy for HNSCC.